Anchoring mesoporous Fe3O4 nanospheres onto N-doped carbon nanotubes toward high-performance composite electrodes for supercapacitors. Issue 14 (1st October 2020) - Zhang, Xiaoliang; Yang, Wenshu; Liu, Aifeng; Guo, Zengcai; Mu, Jingbo; Hou, Junxian; Che, Hongwei
Abstract: Fe-based oxide electrodes for practical applications in supercapacitors (SCs) suffer from low conductivity and poor structural stability. To settle these issues, we report on the design and synthesis of Fe3 O4 /carbon nanocomposites via firmly anchoring mesoporous Fe3 O4 nanospheres onto N-doped carbon nanotubes (N-CNTs) via C–O–Fe bonds. Mesoporous Fe3 O4 nanospheres are featured by rich electroactive sites and short ion diffusion pathways. The N-CNTs, on the other hand, serve as the scaffolds, which not only provide conductive networks but also suppress the accumulation between mesoporous Fe3 O4 nanospheres as well as alleviate volume changes during charge/discharge cycles. Accordingly, the constructed Fe3 O4 /N-CNTs nanocomposite electrode demonstrates improved specific capacity values of up to 314 C g −1 at 1 A g −1, with 92% retention of the initial capacity after 5000 cycles at 10 A g −1 . In addition, the assembled Fe3 O4 /N-CNTs//active carbon (AC) asymmetric supercapacitor (ASC) device possesses an energy density of 25.3 Wh kg −1, suggesting that the prepared Fe3 O4 /N-CNTs nanocomposites are promising electrode materials for use in SCs.